Assessing Nursing Students' Knowledge of Sleeve Gastrectomy Effects: Menilai Pengetahuan Mahasiswa Keperawatan tentang Efek Gastrektomi Lengan - Samahir Sabri Hamid; Wasfi Dhahir Abid Ali; Maher Abdulameer Atiyah (Universitas Muhammadiyah Sidoarjo, 2024)
This descriptive study assesses the knowledge of gastric sleeve procedures among 55 fourth-year nursing students at the College of Nursing in 2024. Recognizing the crucial role of nurses in managing obesity through surgical interventions, this research aims to identify educational gaps within the nursing curriculum. The students were evaluated using a structured questionnaire focused on their understanding of the procedure's link to obesity factors. Results indicated that the majority of students had a satisfactory knowledge level, with significant mean scores; however, about 25% of the responses—mainly those detailing surgical specifics—showed insufficient knowledge. These findings highlight the need for enhanced educational focus on bariatric surgery in nursing programs to better prepare students for clinical responsibilities in patient care and surgical support. Highlights: Knowledge Level: Majority of students showed good understanding of gastric sleeve procedures. Knowledge Gaps: About 25% lacked detailed surgical knowledge. Educational Implications: Results suggest the need for enhanced bariatric surgery content in nursing curricula. Keywords: Gastrectomy, Obesity, Nursing Education, Bariatric, Knowledge